Influence of Vanadium 4+ and 5+ Ions on the Differentiation and Activation of Human Osteoclasts. (29th August 2017) - König, Matthias A.; Gautschi, Oliver P.; Simmen, Hans-Peter; Filgueira, Luis; Cadosch, Dieter
Abstract : Background . In the pathophysiology of implant failure, metal ions and inflammation-driven osteoclasts (OC) play a crucial role. The aim of this study was to investigate whether vanadium (V) ions induce differentiation of monocytic OC precursors into osteoresorptive multinucleated cells. In addition, the influence of V ions on the activation and function of in vitro generated OC was observed. Methods . Human monocytes and osteoclasts were isolated from peripheral blood monocytic cells (PBMCs). Exposition with increasing concentrations (0–3 μ M) of V4 + /V5 + ions for 7 days followed. Assessment of OC differentiation, cell viability, and resorptional ability was performed by standard colorimetric cell viability assay 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenil)-2H-tetrazolium (MTS), tartrate-resistant acid phosphatase (TRAP) expression, and functional resorption assays on bone slides during a period of 21 days. Results . No significant differences were noted between V4 + /V5 + ions (p > 0.05 ). MTS showed significant reduction in cellular viability by V concentrations above 3 μ M (p < 0.05 ). V concentrations above 0.5 μ M showed negative effects on OC activation/differentiation. Higher V concentrations showed negative effects on resorptive function (allp < 0.05 ) without affecting cell viability. V4 + /V5 + concentrations below 3 μ M have negative effects on OC differentiation/function without affecting cell survival. Conclusion . Vanadium-containing implants may reduce implant failure rate by influencing osteoclast activity at the bone-implant interface. V-ligand complexes might offer new treatment options by accumulating in the bone.